PROFIL KETERAMPILAN KONSELING TEMAN SEBAYA (PEER COUNSELING) ANGGOTA PUSAT INFORMASI KONSELING REMAJA (PIK R) MELALUI JALUR PENDIDIKAN DI KOTA DEPOK - Nur Asri Fitriani; Lara Fridani; Anan Sutisna (Jurnal Pendidikan, 2019)
This study aims to determine the peer-counselling skills profile who are the members of PIK R (Youth Counselling Information Center), Educational Pathways in Depok. This research used a quantitative approach with a survey method. The samples were selected by using non-probability sampling, saturation sampling technique applied. The sample of the research is all the members of PIK R Educational Pathways in Depok. The respondents are from public junior high school of SMP Negeri 1 (13 students), public junior high school of SMP Negeri 2 (12 students), public junior high school of SMP Negeri 5 (17 students), public vocational school of SMK Negeri 1 (37 students and public senior high school of SMA Negeri 1 (26 students). The instrument used was the Counselor Competencies Scale – Revised consisting of 12 assessment indicators, in which each indicator has 5 statements. Categorization in this study uses a Likert scale with 5 answer choices. The results of the study showed as follows: overall categorization value that the counseling skills of PIK R members exceeding expectations by 25%, meeting expectations by 37%, approaching expectations by 30%, below expectations by 6%, and endangering by 1%. The highest categorization results regarding the peer-counseling skills profile of PIK R members have met expectations of 37%. Therefore, it indicates that the peer counselors of PIK Depok members have knowledge, skills, consistent traits, and they are proficient in counseling skills. The result met the objectives of the Generation Planning Program (GenRe) training activities for peer educators and PIK R peer counselors, namely to improve the knowledge, attitudes and behavior of peer educators and counselors in the GenRe program in managing and developing Indonesian youth PIK, particularly in Depok.